Renegotiating Academic Integrity in the Age of Generative AI: A Case Study of the “Thinking Partner” Model in High School Learning - Fathor Rohman; Ahmad Silmul Fuady (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2026)
The emergence of Generative Artificial Intelligence in secondary education has intensified concerns regarding academic integrity, particularly in argumentative writing practices. This study aims to examine how the Thinking Partner model, which positions AI as a dialogic cognitive partner, can reconstruct academic integrity while enhancing students’ critical reasoning. Employing a qualitative case study design, the research was conducted in one eleventh-grade class at a public senior high school in East Java involving 28 students engaged in structured AI-assisted argumentative tasks. Data were collected from student–AI interaction transcripts, written argumentative outputs, and reflective journals, and analyzed using thematic analysis through iterative coding that combined inductive theme development with deductive alignment to the cognitive partnership framework. The findings indicate a marked shift from output-oriented AI use toward dialogic engagement characterized by questioning, counter-argument testing, and reflective revision. This transformation corresponded with increased argumentative complexity and the development of internalized intellectual ownership. The study concludes that structured and transparent AI integration does not inherently undermine academic integrity; rather, it can reinforce reflective accountability within Islamic Religious Education learning contexts.